Exploring Teachers’ Representations of Giftedness in Education: Development and Validation of the QPLUS Questionnaire - Giuliani, Arianna; Treglia, Eugenia; Emanuel, Federica (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
This paper addresses the issue of giftedness, joining the debate on how to recognise, preserve and enhance its specific characteristics in school and educational contexts (Cassibba, & Semeraro, 2020; Gagné, 2015). Assuming that teachers’ knowledge, opinions and attitudes play a crucial role in shaping teaching practices and educational pathways (Klassen & Chiu, 2010; Ivarsson, 2023), the study aimed to develop a tool that could detect these dimensions systematically and isn a culturally relevant way. The tool was designed to be user-friendly and functional within initial and in-service teacher training programmes. The paper therefore presents the characteristics of the Questionnaire on Representations and Opinions on Giftedness in Educational and Social Contexts (Q-PLUS), which was developed by translating and adapting the 34-item version of the Opinions about the Gifted and their Education Questionnaire (Gagné & Nadeau, 1985; Gagné, 2018). In conjunction with the Exploratory Factor Analysis of the tool, which was conducted on data collected from a sample of 1.539 secondary school teachers and future teachers, the paper provides detailed insights into the factorial restructuring of the Italian tool and highlights its potential applications. The primary findings from using the instrument show that, while the cognitive and social abilities of gifted students are widely recognised, their emotional and relational vulnerabilities are frequently overlooked due to stereotypes and oversimplifications. The data also confirm a limited level of regulatory and theoretical knowledge on the subject, highlighting a training gap that risks translating into partial or fragmented educational practices.